Theoretical-limit exceeded capacity of the N2+H2 plasma modified graphite anode material. (May 2019) - He, M.; Zhou, H.P.; Ding, G.Q.; Zhang, Z.D.; Ye, X.; Cai, D.; Wu, M.Q.
Abstract: In this paper, we reported a plasma-based modification of the graphite powders as an anode material in lithium ion batteries, resulting in a theoretical-limit exceeded capacity. N2 +H2 plasma treatment conducted in a low-frequency inductively coupled plasma source causes significant modifications in the graphite powders, such as the nanostructured surface, more surface defects, and the slightly widened interplanar spacing. Especially, the plasma generated N atoms from N2 precursor gas were efficiently introduced into the lattice sites of graphite in various configurations of pyridinic N, pyrrolic N and quaterrary N. These modifications lead to a pronounced improvement of electrochemical performance of the graphite powders. The specific reversible capacity is as high as 444 mAh g −1 at 100 mA g −1 for 100 cycles. The higher-rate performance and long-circle stabilities are also significantly improved just by this plasma processing. The charge transfer resistance is consistently reduced in all the cases of N2, H2, and N2 +H2 plasma treatments. The underlying mechanism is analyzed in combination with the plasma diagnostics method of optical emission spectrum. Graphical abstract: Image 105